Nonmotor Symptoms in Parkinsons Disease: Its Relationship with Age of Onset, Duration and Stage of Disease and the Dose and Duration of Levodopa Usage - Ali, M Ahmed; Haque, Anisul; Anwarulla, AKM; Ahmad, Quamruddin (TAJ: Journal of Teachers Association, 2009)
Parkinson's disease is a disease of motor manifestations but non-motor symptoms are also common in Parkinson's disease. Little emphasis is put on non-motor symptoms of PD and there is little data on the relationship of non-motor symptoms to different aspects of the patient and the disease. In this study the relationship of non-motor symptoms to age at onset, duration and stage of the disease, and dose and duration of levodopa use are studied. 128 patients of PD were studied for non-motor symptoms. 111 patients had different types of sensory, autonomic or psychiatric symptoms. Sensory and autonomic symptoms were significantly more common in patients with early age of disease onset and more prolonged duration of the disease, but psychiatric symptoms had no relationship with these factors. In this study it was also found that the frequencies of non-motor symptoms were related to the stage of the disease, longer the duration of the disease more and more non-motor symptoms appear so that 100% patients in stage 5 of the disease had non-motor symptoms. Also sensory and autonomic symptoms were significantly more common in patients with longer duration and higher dose of levodopa use but psychiatric symptoms were significantly commoner in patients with prolonged duration of levodopa use but not to dose of levodopa used. doi: 10.3329/taj.v21i1.3211 TAJ 2008; 21(1): 12-17